2018
DOI: 10.1117/1.jmi.5.2.024004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small traumatic hemorrhages using a computer-generated average human brain CT

Abstract: Abstract. Computed tomography is a standard diagnostic imaging technique for patients with traumatic brain injury (TBI). A limitation is the poor-to-moderate sensitivity for small traumatic hemorrhages. A pilot study using an automatic method to detect hemorrhages <10 mm in diameter in patients with TBI is presented. We have created an average image from 30 normal noncontrast CT scans that were automatically aligned using deformable image registration as implemented in Elastix software. Subsequently, the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It was reported in 1977 by Koo and La Roque (6) that neuropathological changes in hemorrhagic contusion can be visualized by CT. Currently, cranial CT is the ideal method for the diagnosis of CC in the first 24 hours after trauma (12,16,(31)(32)(33)(34)(35). It was reported that the increase in the volume of traumatic cerebral hemorrhage occurs in the first few hours after the trauma in 38 to 59% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in 1977 by Koo and La Roque (6) that neuropathological changes in hemorrhagic contusion can be visualized by CT. Currently, cranial CT is the ideal method for the diagnosis of CC in the first 24 hours after trauma (12,16,(31)(32)(33)(34)(35). It was reported that the increase in the volume of traumatic cerebral hemorrhage occurs in the first few hours after the trauma in 38 to 59% of the cases.…”
Section: Discussionmentioning
confidence: 99%